Basic quantum mechanics - Ghatak Ajoy (New Delhi Macmillan India, 2002)
This book presents the basic concepts in quantum mechanics with emphasis on application in areas like atomic and molecular spectroscopy, quantum well structures, nuclear physics, astrophysics, solid state physics, etc. This is followed by a discussion on
Keywords: Quantum mechanics